Parallel computing in genetic algorithm (GA) with the parallel solution of n Queen’s Problem based on GA in multicore architecture - Saxena S.; Sharma N.; Sharma S. (My University, 2025)
Genetic algorithm (GA) is a commanding stochastic optimization technique, which mimics the progression in the living nature with the aim to solve practical problems. It has been successfully applied to solve the several techniques like problem of scheduling, optimization, feature extraction etc. Effective execution of high performance computing or parallel processing makes this technique more valuable. Parallel implementation is very advantageous for the different time consuming process steps of GA. Till now, there have been proposed numerous approach of parallel implementation of genetic algorithm and plenty of research is going on. Main objective of this paper is to summarize existing techniques of parallel accomplishment of GA with the brief introduction of parallel computing and its tools and techniques and to demonstrate significant contribution of parallel computing in GA. This paper also proposed a parallel solution of n queen‟s problem with significant speedup using GA on easily available multi core architecture. Another main purpose of this paper is to describe the application of parallel GA in medical imaging. © Research India Publications.